2019
DOI: 10.1002/hipo.23138
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of stress reactivity and rapid eye movement sleep theta activity on emotional memory formation

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(60 citation statements)
references
References 99 publications
2
54
0
Order By: Relevance
“…In this sense, being weakly encoded may be low in the hierarchy, and only be consolidated after other information with more "important" tags has been consolidated. Relatedly, a number of studies have implicated REM sleep in emotional memory consolidation (Nishida et al, 2009;van der Helm et al, 2011;Groch et al, 2013;Kim et al, 2019). Our findings on initial encoding strength imply NREM processes, suggesting that different prioritization tags or tags on different types of memories may be read during different stages of sleep.…”
Section: Discussionsupporting
confidence: 57%
“…In this sense, being weakly encoded may be low in the hierarchy, and only be consolidated after other information with more "important" tags has been consolidated. Relatedly, a number of studies have implicated REM sleep in emotional memory consolidation (Nishida et al, 2009;van der Helm et al, 2011;Groch et al, 2013;Kim et al, 2019). Our findings on initial encoding strength imply NREM processes, suggesting that different prioritization tags or tags on different types of memories may be read during different stages of sleep.…”
Section: Discussionsupporting
confidence: 57%
“…For analyses of coupling, one participant from the stress group had their data excluded on the basis of being an outlier (>3SD from the mean). Although behavioral results, including efficacy of the TSST in evoking stress, are reported in our previous publication (Kim et al, 2019), we summarize them briefly here. Memory at the recognition test was significantly better for emotional compared to neutral items (t (63) = 2.67, p = .010), a pattern that was true for both negative (t (63) = 2.57, p = .013) and positive (t (63) = .2.28, p = .026) images.…”
Section: Discussionmentioning
confidence: 99%
“…Although much research has linked the consolidation of emotional memories to rapid eye movement sleep (Groch et al, 2013;Kim et al, 2019;Nishida et al, 2009;Sopp et al, 2017;Wagner et al, 2001), newer work suggests SWS plays a role as well (Alger et al, 2018;Kim & Payne, 2020;Payne et al, 2015). In fact, several studies have found relationships between emotional memory and SWS but not REM sleep, raising the question of whether SWS and REM sleep differentially contribute to emotional memory consolidation (Benedict et al, 2009;Payne, 2011Payne, ,, 2014Payne et al, 2015;Wagner et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sleep disruptions may, in turn, contribute to effects of stress on memory, affect, autonomic and immune functions. Several recent studies suggest that REM theta and non-REM sharp wave ripple frequencies may serve as useful biosignatures for stress-mediated alterations in brain function (Girardeau et al, 2017;Kim et al, 2019;Nolett et al, 2019).…”
Section: Speeding Translationmentioning
confidence: 99%